Postmortem 7T MRI for guided histopathology and evaluation of cerebrovascular disease. Issue 1 (7th November 2022) - Lahna, David; Roese, Natalie; Woltjer, Randy; Boespflug, Erin L; Schwartz, Daniel; Grinstead, John; Dodge, Hiroko H; Wall, Rachel; Kaye, Jeffrey A; Rooney, William D; Silbert, Lisa C
Abstract: Postmortem (PM) magnetic resonance imaging (MRI) can serve as a bridge between in vivo imaging and histology by connecting MRI observed macrostructural findings to histological staining and microstructural changes. Data were acquired from 20 formalin-fixed brains including T2, T1, PD, and T2*-weighted images of left hemispheres and 6-mm-thick coronal slices. Tissue slices were bisected, aligned to MR images and used to guide histological sampling. Markers of myelin and oligodendroglia alterations were semiquantitatively rated and compared within white matter hyperintensities (WMHs) and normal-appearing white matter. Tissue priors were created from 3T in vivo data and used to guide segmentation of WMH. PM WMH and hemisphere volumes were compared to volumes derived from in vivo data. PM T2 WMH and T1 hemisphere volumes were correlated with in vivo 3T FLAIR WMH and T1 hemisphere volumes. WMH showed significant myelin loss, decreased GFAP expression and increased vimentin expression. MR-visible perivascular spaces and cortical microvascular lesions were successfully captured on histopathological sections. PM MRI can quantify cerebrovascular disease burden and guide tissue sampling, allowing for more comprehensive characterization of cerebrovascular disease that may be used to study etiologies of age-related cognitive change.